Genetically diverse populations spread faster in benign but not in challenging environments. Issue 6 (3rd May 2021) - Mortier, Frederik; Masier, Stefano; Bonte, Dries
Abstract: Population spread from a limited pool of founding propagules is at the basis of biological invasions. The size and genetic variation of these propagules eventually affect whether the invasion is successful or not. The inevitable bottleneck at introduction decreases genetic diversity, and therefore should affect population growth and spread. However, many heavily bottlenecked invasive populations have been successful in nature. Negative effects of a genetic bottleneck are typically considered to be relaxed in benign environments because of a release from stress. Despite its relevance to understand and predict invasions, empirical evidence on the role of genetic diversity in relation to habitat quality is largely lacking. We use the mite Tetranychus urticae Koch as a model to experimentally assess spread rate and size of genetically depleted inbred populations vs. enriched mixed populations. This was assessed in replicated linear patch systems consisting of benign (bean), challenging (tomato), or a gradient (bean to tomato) habitat. As expected, we found no effect of genetic diversity on population size in benign habitat but found that it increased population size in challenging habitat. However, we found that population spread rates were increased due to genetic diversity in the benign but not in the challenging habitat. Additionally, variance in spread was consistently higher in genetically poor populations and highest in the challenging habitat. Our experiment challenges the general view that a bottleneck in genetic variation decreases invasion success in challenging but not benign environments.